Identification of pathways and genes in the process of E6/E7‐induced carcinogenesis of esophageal epithelial cells. Issue 12 (17th February 2020) - Xia, Yang; Li, Jintao; Li, Shuying; Khodahemmati, Sara; Ghaffar, Maliha; Chen, Su; Sheng, Wang
Abstract: Human papillomavirus (HPV) infection was associated with some carcinomas, especially malignant tumors in upper digestive tract, upper respiratory tract, and genitourinary system. The mechanism of the viral transformation of normal cells is still not very clear. To investigate the tumorigenesis of epithelial cells, E6/E7‐induced malignant transformation model cells were used for expression profiling analysis by performing RNA expression microarray detection. Bioinformatics analysis was applied to investigate the cellular process changes along with the E6/E7 expression in SHEE cells. The differentially expressed genes were further grouped and uploaded for Search Tool for the Retrieval of Interacting Genes analysis. The protein‐protein interaction results were visualized. The hub genes and their first‐neighbors genes were selected, followed by gene ontology and Kyoto Encyclopedia of Genes and Genomes pathway analysis. The obtained results demonstrated that tumor‐related biological processes began to emerge during the carcinogenesis process from 48th passage to 76th passage of SHEE cells after E6/E7 expression. Ten hub genes were identified and analyzed during the E6/E7‐induced tumorigenesis. This study explores the gene expression network in the progressive transformation of immortalized esophageal epithelial cells induced by E6/E7 expression. Understanding the biological processes and hub genes that first appear during the transformation will provide some clues to the mechanism of E6/E7‐induced carcinogenesis of esophageal epithelial cells. Research Highlights: E6/E7 expression was involved in malignant transformation of SHEE cells. Based on KEGG pathway analysis, the initiation of tumorigenesis of SHEE cells was indicated. Some novel differentially expressed genes in the carcinogenic process were identified.